Lipid-coated hydrogel shapes as components of electrical circuits and mechanical devices - Sapra, K; Bayley, H (Springer Nature, 2012)
Recently, two-dimensional networks of aqueous droplets separated by lipid bilayers, with engineered protein pores as functional elements, were used to construct millimeter-sized devices such as a light sensor, a battery, and half- and full-wave rectifiers. Here, for the first time, we show that hydrogel shapes, coated with lipid monolayers, can be used as building blocks for such networks, yielding scalable electrical circuits and mechanical devices. Examples include a mechanical switch, a rotor driven by a magnetic field and painted circuits, analogous to printed circuit boards, made with centimeter-length agarose wires. Bottom-up fabrication with lipid-coated hydrogel shapes is therefore a useful step towards the synthetic biology of functional devices including minimal tissues.